The Impact of Social Media on Economic Growth: Empirical Evidence of Facebook, YouTube, Twitter and Pinterest - Vitenu-Sackey, Prince Asare (International Journal of Business, Economics and Management, 2020)
The study assessed the impact of social media on economic growth in a global perspective hence the use of 198 countries as sample for the period 2009 - 2017. The study utilised and adopted panel data methodologies such as panel corrected standard errors, two-stage least square and panel quantile regression methods for its regression analysis. The study’s theoretical basis was on the endogenous growth model. The findings of the study support the two hypothesis that exist between social media and economic growth nexus. In relevance, the study concludes that social media has both positive and negative impact on economic growth perhaps fixed broadband, number of internet users and secure internet servers are the major drivers of social media. In particular, the study found that Facebook and Pinterest negatively affect economic growth as this finding is in support of the second hypothesis of social media and economic growth nexus. The positive relationship finding supports the first hypothesis that the abolishment of barriers to entry to enable users of social media to publish and disseminate information without any limitations with the support of proper and efficient internet and broadband supply then social media could positively affect economic growth because the multiplicity of media such as wikis, blogs, pictures, videos etc. to a large extent propel the potential of social media in relation to dissemination of information and knowledge whereas ensuring a multi-channel diffusion and codification of knowledge as YouTube and Twitter showed positive and significant impact on economic growth.